Workflow of the zero‐fluoro pulsed field ablation - Shu Hirata; Koichi Nagashima; Ryuta Watanabe; Yuji Wakamatsu; Moyuru Hirata; Sayaka Kurokawa; Naoto Otsuka; Masanaru Sawada; Yasuo Okumura (Journal of Arrhythmia)
Abstract Background Zero‐fluoroscopic pulsed field ablation (PFA) is the next step in advancing pulmonary vein isolation (PVI) for atrial fibrillation (AF). Methods A workflow incorporating a variable‐loop circular PFA catheter, intracardiac echocardiography (ICE), and a visualized sheath was applied to 15 paroxysmal AF patients. Results It consisted of three steps: (1) positioning a non‐magnetic mapping catheter in the coronary sinus after creating a right atrial matrix, (2) transseptal puncture with the sheath advancement to the left atrium under ICE guidance, and (3) PFA confirming catheter‐tissue contact with tissue proximity indication. Conclusions This zero‐fluoro PFA workflow is feasible without advanced technique.